Antimonate sequestration from aqueous solution using zirconium, iron and zirconium-iron modified biochars - Md. Aminur Rahman (Nature Portfolio, 2021)
Abstract Antimony (Sb) is increasingly being recognized as an important contaminant due to its various industrial applications and mining operations. Environmental remediation approaches for Sb are still lacking, as is the understanding of Sb environmental chemistry. In this study, biosolid biochar (BSBC) was produced and utilized to remove antimonate (Sb(V)) from aqueous solution. Zirconium (Zr), Zirconium-iron (Zr–Fe) and Fe–O coated BSBC were synthesized for enhancing Sb(V) sorption capacities of BSBC. The combined results of specific surface area, FTIR, SEM–EDS, TEM–EDS, and XPS confirmed that Zr and/or Zr–Fe were successfully coated onto BSBC. The effects of reaction time, pH, initial Sb(V) concentration, adsorbate doses, ionic strength, temperature, and the influence of major competitive co-existing anions and cations on the adsorption of Sb(V) were investigated. The maximum sorption capacity of Zr–O, Zr–Fe, Zr–FeCl3, Fe–O, and FeCl3 coated BSBC were 66.67, 98.04, 85.47, 39.68, and 31.54 mg/g respectively under acidic conditions. The XPS results revealed redox transformation of Sb(V) species to Sb(III) occurred under oxic conditions, demonstrating the biochar’s ability to behave as an electron shuttle during sorption. The sorption study suggests that Zr–O and Zr–O–Fe coated BSBC could perform as favourable adsorbents for mitigating Sb(V) contaminated waters.